2016
DOI: 10.1165/rcmb.2016-0002rc
|View full text |Cite
|
Sign up to set email alerts
|

A Recently Established Murine Model of Nasal Polyps Demonstrates Activation of B Cells, as Occurs in Human Nasal Polyps

Abstract: Animal model systems are invaluable for examining human diseases. Our laboratory recently established a mouse model of nasal polyps (NPs) and investigated similarities and differences between this mouse model and human NPs. We especially focus on the hypothesis that B cell activation occurs during NP generation in the murine model. After induction of ovalbumin-induced allergic rhinosinusitis, 6% ovalbumin and Staphylococcus aureus enterotoxin B (10 ng) were instilled into the nasal cavity of mice three times p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
(25 reference statements)
1
15
1
Order By: Relevance
“…This discrepancy could possibly be due to the fact that we measured the thickness of the mature olfactory neuron layer, whereas Khalmuratova et al investigated the subepithelial layer. Further, nasal polypoid lesions described by Kim et al were not observed in our HDM + SEB‐treated group, and this was corroborated by qPCR analysis, showing low B‐cell activating factor (BAFF) mRNA levels and no modification of A proliferation‐inducing ligand (APRIL) mRNA, both markers of nasal polyps in humans and mice …”
Section: Discussionsupporting
confidence: 85%
“…This discrepancy could possibly be due to the fact that we measured the thickness of the mature olfactory neuron layer, whereas Khalmuratova et al investigated the subepithelial layer. Further, nasal polypoid lesions described by Kim et al were not observed in our HDM + SEB‐treated group, and this was corroborated by qPCR analysis, showing low B‐cell activating factor (BAFF) mRNA levels and no modification of A proliferation‐inducing ligand (APRIL) mRNA, both markers of nasal polyps in humans and mice …”
Section: Discussionsupporting
confidence: 85%
“…In fact, the number of mast cells in the OVA plus SEB model in both BALB/c and B6 mice was around 5 cells/high power field (HPF) and in the HDM plus SEB model was nearly 20 mast cells per HPF in nasal mucosa . Most recently, Kim et al showed that this NP mouse model demonstrated enhanced B‐cell responses reminiscent of B cell responses in human NP …”
Section: Resultsmentioning
confidence: 99%
“…To confirm and fully investigate IL‐13Rα2's mechanism that contributes to polypogenesis, future experiments using IL‐13Rα2 knockout or overexpression cell or animal models can be employed to observe their responses to IL‐13 leading to subsequent polypogenesis and its associated features. Additionally, the knockout of IL‐13Rα2 using antibodies or locked nucleic acid (LNA) RNAi strategies could be further applied to a recently established mouse nasal polyp model to observe IL‐13Rα2's role in accelerating polyp formation…”
Section: Discussionmentioning
confidence: 99%